Ergovaline in populations of endophyte infected Festuca rubra subsp. pruinosa - Vázquez de Aldana, Beatriz R.; Zabalgogeazcoa, Iñigo; García Ciudad, Antonia; García Criado, Balbino (European Grassland Federation, 2006)
Festuca rubra subsp. pruinosa is a grass whose preferred habitat are coastal cliffs, a harsh environment where plants grow in cavities and are exposed to salt water spray. This grass species is systemically infected by the fungal endophyte Epichloë festucae and the interaction is asymptomatic. Endophyte infected grasses produce several alkaloids toxic to herbivores. In a previous work, we showed that an average of 69% of Festuca rubra subsp. pruinosa plants from cliff ecosystems (in the North Atlantic coast of Galicia region –Spain-) were infected by the endophyte Epichloë festucae. The main objective in this study was to determine whether endophyte infected plants of F. rubra pruinosa produce the ergovaline alkaloid, which is toxic to large herbivores. For this purpose infected plants of F. rubra pruinosa, from four populations and at two different harvests were analysed for the presence of ergovaline. An average of 80% of the analysed plants, which were endophyte infected, contained ergovaline. The alkaloid was detected in the four populations. The concentration ranged from 0.05 – 0.58 μg g-1 in the first harvest and between 0.06 and 1.90 μg g-1 in the second. The mean ergovaline content increased from the first (0.14 μg g-1) to the second harvest (0.35 μg g-1). This work was funded by the Spanish Ministry of Education and Science (‘PN Investigación Científica Desarrollo e Innovación Tecnológica’) + FEDER (AGL2002-02766 AGR-FOR).